Coping with global warming: Adult thermal thresholds in four pestiferous Anastrepha species determined under experimental laboratory conditions and development/survival times of immatures and adults under natural field conditions - Guillén, Larissa; Pascacio-Villafán, Carlos; Osorio-Paz, Ixchel; Ortega-Casas, Rafael; Enciso-Ortíz, Erick; Altúzar-Molina, Alma; Velázquez, Olinda; Aluja, Martín (Frontiers in Physiology, 2022)
Climate change, particularly global warming, is disturbing biological processes in unexpected ways and forcing us to re-study/reanalyze the effects of varying temperatures, among them extreme ones, on insect functional traits such as lifespan and fecundity/fertility. Here we experimentally tested, under both laboratory and field conditions, the effects of an extreme range of temperatures (5, 10, 15, 20, 30, 40, and 45°C, and the naturally varying conditions experienced in the field), on survivorship/lifespan, fecundity, and fertility of four pestiferous fruit fly species exhibiting contrasting life histories and belonging to two phylogenetic groups within the genus Anastrepha: A. ludens, A. obliqua, A. striata, and A. serpentina. In the field, we also measured the length of the entire life cycle (egg to adult), and in one species (A. ludens), the effect on the latter of the host plant (mango and grapefruit). Under laboratory conditions, none of the adults, independent of species, could survive a single day when exposed to a constant temperature of 45°C, but sexually mature A. striata and A. serpentina females/males survived at the highly contrasting temperatures of 5 and 40°C at least seven days. Maximum longevity was achieved in all species at 15°C (375, 225, 175 and 160 days in A. ludens, A. serpentina, A. striata and A. obliqua females, respectively). Anastrepha ludens layed many eggs until late in life (368 d) at 15°C, but none eclosed. Eclosion was only observed in all species at 20 and 30°C. Under natural conditions, flies lived ca. 100 days less than in the laboratory at 15°C, likely due to the physiological cost of dealing with the highly varying environmental patterns over 24 h (minimum and maximum temperatures and RH of ca. 10 - 40°C, and 22 - 100%, respectively). In the case of A. ludens, the immature's developmental time was shorter in mango, but adult survival was longer than in grapefruit. We discuss our results considering the physiological processes regulating the traits measured and tie them to the increasing problem of global warming and its hidden effects on the physiology of insects. We also discuss the ecological and pest management implications.